Phallus prolapse in a sulcata tortoise (Centrochelys sulcata) at Batu Secret Zoo, East Java - Azzahra, Rifa Rahma; Putri, Hana Mitsuki; Restanti, Prista Dwi; Fahmiantika, Reza; Hardian, Rizky; Mohamad, Kusdiantoro (Journal of Wildlife and Conservation Medicine, 2025)
Background In Sulcata tortoises (Centrochelys sulcata), the phallus naturally extends through the cloaca during mating. However, excessive and persistent phallus protrusion, often due to aggressive mating behavior, increases the risk of prolapse.Objective This case report describes phallus prolapse in a Sulcata tortoise at Batu Secret Zoo, East Java, Indonesia.Case A male Sulcata tortoise, over 15 years old and weighing 30 kg, exhibited frequent aggressive behavior during the mating season. On August 30, 2024, the keeper reported a tortoise's phallus protruding from the cloaca. Physical examination revealed a necrotic phallus surrounded by abscesses. A blood smear examination suggested anemia. The patient was diagnosed with phallus prolapse caused by mating-related trauma.Treatment Minor surgical debridement was performed to remove necrotic tissue and abscesses associated with hyperkeratinization and inflammation. Postoperative care included a 7-day course of antibiotics, multivitamins, lactated Ringer’s solution with glucose infusion, and haematodin.Conclusion Minor surgery succeeded in repositioning the phallus within the cloaca, and the tortoise exhibited healthy clinical signs after seven days of postoperative care.